Fighting gentrification in the neoliberal university: Displacing communities, researchers and the very possibility of radical critique. (August 2016) - Ferreri, Mara; Glucksberg, Luna
The demolition of social housing figures prominently in the most recent wave of state-led gentrification in London: fighting these processes as academics and activists presents ethical, methodological and strategic issues. We have chosen to address these issues by cautiously drawing a symbolic parallel between the conditions faced by social tenants in London, threatened with the destruction of their homes and communities, and the challenges faced by researchers who study and work within these communities, often on part-time, temporary and insecure contracts, themselves under threat of eviction from the very city they research and from academia. Navigating professional precarity and the precarity of place, we stress the need for longitudinal and ethnographic research into the effects of demolition and regeneration, whilst warning against critical urban research becoming more and more the province of tenured middle class scholars.